Concesión de asilo político a sentenciados según la convención de viena - Jalon Cedeño, Luis Carlos (2025)
This research focuses on analyzing the complex relationship between the right to political asylum and diplomatic protection through the case study between Ecuador and Mexico. It examines the tensions that arise when granting asylum to convicted criminals within the framework of the Vienna and 1954 Asylum Conventions. Using a qualitative and comparative approach, legal documents, international treaties, jurisprudence, and practical cases were analyzed. Additionally, interviews with international law experts were conducted to enrich the analysis. The findings reveal that granting asylum to convicted criminals creates conflicts with the 1954 Convention, which restricts asylum to those who have not committed common crimes. However, some states adopt more flexible interpretations, potentially leading to diplomatic tensions. On the other hand, the Vienna Convention establishes robust protection for diplomatic missions. Nevertheless, granting asylum under these circumstances may jeopardize this protection, creating conflicts between state obligations. In conclusion, the research highlights the need for a more harmonized interpretation of both conventions. It recommends strengthening international dialogue, revising legal frameworks, and establishing clearer criteria for granting asylum, thereby ensuring a balance between the protection of human rights and respect for international law.